Development of an Analytical Procedure for the Determination of Multiclass Compounds for Forensic Veterinary Toxicology. Issue 3 (29th November 2017) - Sell, Bartosz; Sniegocki, Tomasz; Zmudzki, Jan; Posyniak, Andrzej
Abstract: Reported here is a new analytical multiclass method based on QuEChERS technique, which has proven to be effective in diagnosing fatal poisoning cases in animals. This method has been developed for the determination of analytes in liver samples comprising rodenticides, carbamate and organophosphorus pesticides, coccidiostats and mycotoxins. The procedure entails addition of acetonitrile and sodium acetate to 2 g of homogenized liver sample. The mixture was shaken intensively and centrifuged for phase separation, which was followed by an organic phase transfer into a tube containing sorbents (PSA and C18) and magnesium sulfate, then it was centrifuged, the supernatant was filtered and analyzed by liquid chromatography tandem mass spectrometry. A validation of the procedure was performed. Repeatability variation coefficients <15% have been achieved for most of the analyzed substances. Analytical conditions allowed for a successful separation of variety of poisons with the typical screening detection limit at ≤10 μg/kg levels. The method was used to investigate more than 100 animals poisoning incidents and proved that is useful to be used in animal forensic toxicology cases.